Effects of Monochromatic and Composite Light Withering on Black Tea Aroma - Yafang Li; Bilin Li; Ziyan Zhu; Wushuang Zhang; Jingwen Yang; Wei Xu; Ling Lin (Foods, 2025)
In this study, the effects of different monochromatic (red, blue, and yellow light) and composite (red–blue and red–yellow) LED light withering on the aroma of black tea was investigated. The results showed that among monochromatic LED treatments, red light withering achieved the highest sensory evaluation score for aroma. However, yellow light withering enhanced soluble sugar content and reduced tea polyphenol levels. It also increased the total amount of volatile compounds more effectively than red or blue light treatments. Nevertheless, single-wavelength LED withering was less effective than natural light in aroma improvement. In contrast, composite light withering outperformed single-wavelength LED treatments in improving black tea aroma, with the red–yellow light combination being more pronounced. It elevated the level of hydrocarbons, certain aldehydes, and alcohols, which ultimately impart an almond-like and roasted aroma profile to the black tea. The findings suggested that appropriate composite light withering can effectively improve the aroma of black tea.